Robust Optimization of Multiple Microgrids Scheduling for Integrated Energy System with Uncertain Sources and Loads. Issue 1 (August 2020) - Hou, Lei; Tian, Ersheng; Zhou, Yibin; Lu, Pengcheng; Wang, Taowei; Zhang, Yusen; Liu, Zhe; Yang, Yexin; Li, Peng
Abstract: With the rapid development of integrated energy system and microgrid technologies, aiming at the operational safety problems caused by the uncertainty of the sources and loads, this paper proposed a robust optimal scheduling model of the multiple integrated energy microgrids considering sources and loads uncertainty. In order to minimize the total operating cost of the multiple microgrids, the interconnection lines were introduced into the multiple microgrids for joint operation, on the basis of renewable energy outputs and multi-energy loads prediction, the uncertainty of sources and loads were characterized and the established model were solved. The results of an example showed that the proposed method can effectively improve the economy of multiple microgrids and reduce the risk caused by the uncertainty of sources and loads, thus verified the effectiveness and feasibility of the proposed method.